The spatial effect of digital economy on public psychological resilience during the diffusive crisis - Tao, Jiancong; Wang, Zhe; Li, Junwei (Frontiers in Public Health, 2023)
Purpose: To explore the spatial effects and spatial heterogeneity of information media on public psychological resilience in the digital economy using spatial econometric models. Methods: This study is based on the Baidu Search Index from 2011 to 2020 and the provincial panel data of 30 provinces in China. It constructs measures of public psychological resilience and digital economy development level and employs the spatial Durbin model to empirically analyze the relationship between the two, revealing their spatial impact. Results: (1) Public psychological resilience exhibits a spatial distribution characterized by high values in the west, medium values in the central region, and low values in the east, while the digital economy development level shows a "U"-shaped spatial structure with high levels in the eastern and western regions and low levels in the middle; (2) The digital economy development level in a local region has a negative effect on the public psychological resilience of that region, while the digital economy development level in surrounding regions has a positive spatial spillover effect on the local region's public psychological resilience. Conclusions: It is essential to strengthen crisis management, focus on the coordinated development of the digital economy in different regions, share the benefits of digital society development more equitably and broadly, and further improve the psychological resilience of regions under the context of digital economy development.